Kala-azar without splenomegaly: A rare presentation - Agrawal, Suraj; Tahlan, Anita; Singla, Mandeep; Lehl, SS (Indian Journal of Case Reports, 2019)
Visceral leishmaniasis is a major public health problem in Bangladesh, North East India, Nepal, Sudan and North East Brazil. In India, leishmaniasis is more prevalent in Bihar, Jharkhand, West Bengal and Uttar Pradesh. We present the case of a 55-year-old male farmer from Himachal Pradesh with complaints of fever for 2.5 months, appetite loss and weight loss for 1 month. On evaluation, he was found to have pancytopenia, transaminitis, and hyperbilirubinemia. Tropical fever serology and viral markers were negative. Blood and urine cultures were sterile, and ascitic fluid was acellular and high SAAG with normal ADA. Bone marrow was done due to non-responding pancytopenia which reveals intracellular amastigote form of Leishmania Donovani. A final diagnosis of Kala-azar without splenomegaly with moderate ascites was made as an absence of splenomegaly was the most striking aspect in our patient.